Pochówki dziecięce z cmentarzyska kultury wielbarskiej w Odrach - Grzelakowska, Elżbieta (Acta Universitatis Lodziensis. Folia Archaeologica, 1991)
The present article attemps to confront the data from anthropological and archaeological sources from sets of the grave exploited during studies on the burials ground of Wielbark culture in Odry in 1972-1978. As a result of this confrontation it can be concluded that children’s graves situated in this burials ground can be dated for the whole period of its use. Within the site they do not constitute the distinguishing group appearing in from of flat graves as well as grave-mouds. No relation between the age of the dead and the form of the grave he had been buried in was observed. The confrontation or archaeological and anthropological sources allows for the statement that neither the size of the hollow of skeleton graves nor the archaeological material included in it can be the only indicators of the dead’s age. However, in case of the lack of any remains of bones all other data should be considered and criticised. As a result of analysis of burials it can be said that burials classified as children’s ones exceeded 1/3 of all burials.